Loyalty as permission to forgive: sport, political, and religious identification as predictors of transgression diminishment - Towery, Nathan A.; Billings, Andrew C.; Zengaro, Elisabetta C.; Sadri, Sean R. (Frontiers in Communication, 2023)
A national survey of 314 Americans was employed to determine whether core forms of group identification (sport, political, and religious) predict one's likelihood to forgive a leader within that group for an intentional/preventable transgression. Three forms of transgressions (assault & battery, sex with a minor, stealing money) were presented as possible scenarios for leaders of sport, political, and religious groups. Sports leaders were more likely to be forgiven overall, with each of the three scenarios shifting levels of forgiveness; sex with a minor was more likely to be forgiven for sports figures, while stealing money was less likely to be forgiven for religious leaders. Unaffiliated individuals were less likely to forgive transgressions, with no differences between identified groups.